2023
DOI: 10.47352/jmans.2774-3047.165
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of The Anticancer Activity of Hydroxyxanthones Against Human Liver Carcinoma Cell Line

Abstract: Nowadays, cancer is one of the most fatal diseases in developed and developing countries. Therefore, it is an urgent need to find more effective anticancer drugs among the recent commercially available standard drugs. Xanthone derivatives have been researched as anticancer drugs due to their ease of synthesis and structure modification, as well as their excellent anticancer activity. In this work, the in vitro anticancer activity of hydroxyxanthones against the human liver carcinoma cell line (HepG2) was evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…It was reported that Gly695, Gly700, Ala719, Glu767, Met769, Arg812, Asp818, Asp831, Gly833, and Tyr845 play a critical role in the catalytic activity of EGFR protein, especially in the suppression of the division of cancer cells [55]. Additionally, Choowongkomon et al [56] reported that there were five active regions in the binding pocket of EGFR receptor, i.e., sugar pocket region, phosphate binding region, adenine region, hydrophobic I and II regions.…”
Section: Docking Of Xanthone-chalcone Derivativesmentioning
confidence: 99%
“…It was reported that Gly695, Gly700, Ala719, Glu767, Met769, Arg812, Asp818, Asp831, Gly833, and Tyr845 play a critical role in the catalytic activity of EGFR protein, especially in the suppression of the division of cancer cells [55]. Additionally, Choowongkomon et al [56] reported that there were five active regions in the binding pocket of EGFR receptor, i.e., sugar pocket region, phosphate binding region, adenine region, hydrophobic I and II regions.…”
Section: Docking Of Xanthone-chalcone Derivativesmentioning
confidence: 99%